Effects of environmental variables on students’ achievement in mathematics in some selected schools in ila lga Osun State, Nigeria (2013)
The study examines the relationship between some environmental variables and students' achievement in mathematics. The research design adopted for this study was a survey in which 250 senior secondary school III students were sampled through stratified random technique. Mathematics Achievement Test and a questionnaire on environmental variables were used as instruments for data collection. The data collected were analyzed using inferential statistics, Pearson Product Moment Correlation. The findings demonstrate that there was a relationship between economic factor and students' achievement in mathematics. Also; a significant relationship was observed between socio-factor, peer influence and home background and students' achievement in mathematics. It was recommended among others that parents should use their socio-economic status positively whether high or low to influence their children performance in mathematics; and if possible, other subjects. They can do this by making available the necessary materials such as books, learning aids and even writing materials that can enable them to do well in mathematics.